2009
DOI: 10.1245/s10434-009-0599-x
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Stellate Cells Promote Liver Metastasis of Colon Cancer Cells by the Action of SDF-1/CXCR4 Axis

Abstract: These results suggest that HSCs play important role in liver metastasis of colon cancer cells by the action of SDF-1/CXCR4 axis and provide preclinical evidence that blockade of the axis is a target for antimetastasis therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
104
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(114 citation statements)
references
References 26 publications
6
104
0
4
Order By: Relevance
“…To investigate the number of CXCR3-or CXCR4-positive cells, we first chose three arbitrary sites under the microscope (original magnification, 400Â) and counted the cancer cells, as described previously. 12 We then calculated the proportion of CXCR3-or CXCR4-positive cells within the counted region.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…To investigate the number of CXCR3-or CXCR4-positive cells, we first chose three arbitrary sites under the microscope (original magnification, 400Â) and counted the cancer cells, as described previously. 12 We then calculated the proportion of CXCR3-or CXCR4-positive cells within the counted region.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…SDF-1 is expressed by stromal cells, such as fibroblasts and endothelial cells (16). In colorectal cancer, elevated SDF-1 expression is associated with metastasis and poor prognosis (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…CXCL12 is a chemokine expressed by both cancer and stromal cells (21,22). Reportedly, CXCL12 and its receptor, CXCR4, play important roles in local progression, dissemination and immune evasion of colorectal cancer cells (23)(24)(25). Our recent study also suggested that stromal CXCL12 and CXCR4 expression following preoperative CRT is associated with distant recurrence and poor prognosis in RC (15).…”
Section: Univariate Analysismentioning
confidence: 83%